A Secure Web Application for Zura Razak Management System with Image-Based Authentication - Mohd Hisham, Nur Athirah Farhana; Harun, Nur Ziadah (Applied Information Technology And Computer Science, 2026)
Zura Razak’s Enterprise faced issues with its manual order system, such as order delays, inaccurate data handling, and potential threats to customer information security. These problems revealed the need for a more secure and efficient digital solution. In response, a secure web-based system was proposed to replace the manual process. The system incorporates password and image-based authentication, along with encryption, to safeguard sensitive data. With this system, the business aims to process orders more efficiently and accurately while improving data protection. The admin will manage products, sales, categories, orders, customer feedback, and send emails. Customers will log in securely, browse and purchase products, make payments, access order history, submit feedback, and update profiles. The system is designed to enhance efficiency, reduce human error, and strengthen security. Future enhancements may include real-time live chat, shipping integration, and online banking to further improve functionality and user experience.